2014
DOI: 10.1308/003588414x13814021677313
|View full text |Cite
|
Sign up to set email alerts
|

Ionising radiation exposure in paediatric trauma

Abstract: INTRODUCTION Trauma remains the highest cause of paediatric morbidity and mortality. These trauma patients incur radiation exposure during intraoperative management. Medical personnel have the responsibility to ensure observation of the 'as low as reasonably achievable' principle, a practice mandate that minimises ionising radiation exposure. The aim of this study was to quantify the difference in the amount of ionising radiation used by operating surgeons of different grades in paediatric trauma surgery. METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 8 publications
1
8
0
8
Order By: Relevance
“…We found that surgeon experience correlated with radiation exposure. This is in line with the study by Patel et al [ 3 ]. In paediatric orthopaedic trauma cases, they found that consultant surgeons used 51% less screening time and 35% less radiation exposure (as measured by DAP), than junior surgeons.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…We found that surgeon experience correlated with radiation exposure. This is in line with the study by Patel et al [ 3 ]. In paediatric orthopaedic trauma cases, they found that consultant surgeons used 51% less screening time and 35% less radiation exposure (as measured by DAP), than junior surgeons.…”
Section: Discussionsupporting
confidence: 94%
“…To our knowledge, there are only two studies that have attempted to report this. Patel et al [ 3 ] reported screening time and DAP of 782 paediatric trauma cases utilizing fluoroscopy in the operating room. Salvia et al studied the radiation exposure in 80 orthopaedic cases (16 different surgery types).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent quantification study of radiation exposures in 248 children reported that the mean DAP exposure of supracondylar fractures and flexible nailing of the forearm were 22.3 and 26.7 mGy/cm 2 , respectively [ 20 ]. One study documented that the mean DAP of elbow fracture treatments performed by experienced surgeons was 87.41 mGy/cm 2 [ 21 ]. Poor visualization of the radial head and neck, especially in young children, can increase radiation use.…”
Section: Discussionmentioning
confidence: 99%
“…11 Unfortunately, the long-term effects of radiation exposure of this sort are largely unknown, and concern exists that even small doses may be detrimental because they accumulate over the lifespan, with children particularly being nearly 10 times more sensitive than adults. 12 Radiographs also contribute to healthcare expenditure, waiting times, and strains on personnel and resources. 13 Thus, if evidence is strong that routine radiography has minimal utility in patient management, restricting it to patients with clinical indications would not only help decrease radiation exposure but also free resources for other hospital needs.…”
mentioning
confidence: 99%